Radial growth of Balanophyllia elegans as a response to changes in carbonate system parameters DIC, pH, and CO32- - Lau, Samantha (My University, 2017)
The steady, increasing flux of carbon dioxide from the atmosphere into the ocean is posing a major threat to the marine biota that depend on stable pH and chemical concentrations for biomineralization. One important and prevalent organism at risk of these effects of ocean acidification is the cold-water, scleractinian coral, Balanophyllia elegans. The goal of this study was to test the individual significance of carbonate system parameters DIC, pH, and CO32- on the growth and calcification of Balanophyllia elegans. In this experiment, growth was measured radially as the change in diameter over time. Unfortunately, because Balanophyllia elegans is a very slow growing organism and only extends up to a few millimeters during its juvenile state, absolute changes in size are difficult to detect. There were many obstacles encountered in quantifying the true diameters and areas of the samples over time. Difficulties included fine-focusing of the camera, software calibration, and relative selection of the major and minor axes. This study explores the challenges of using live coral imaging to track growth and suggests alternative methods to approach this objective in the future.
Keywords: Balanophyllia elegans; biomineralization; Coral